If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15(E + -3) = -10(E + 2) Reorder the terms: 15(-3 + E) = -10(E + 2) (-3 * 15 + E * 15) = -10(E + 2) (-45 + 15E) = -10(E + 2) Reorder the terms: -45 + 15E = -10(2 + E) -45 + 15E = (2 * -10 + E * -10) -45 + 15E = (-20 + -10E) Solving -45 + 15E = -20 + -10E Solving for variable 'E'. Move all terms containing E to the left, all other terms to the right. Add '10E' to each side of the equation. -45 + 15E + 10E = -20 + -10E + 10E Combine like terms: 15E + 10E = 25E -45 + 25E = -20 + -10E + 10E Combine like terms: -10E + 10E = 0 -45 + 25E = -20 + 0 -45 + 25E = -20 Add '45' to each side of the equation. -45 + 45 + 25E = -20 + 45 Combine like terms: -45 + 45 = 0 0 + 25E = -20 + 45 25E = -20 + 45 Combine like terms: -20 + 45 = 25 25E = 25 Divide each side by '25'. E = 1 Simplifying E = 1
| r(r)+3r=6 | | x^3+3x-14=0 | | 4(7-y)+2y=8 | | x+12=4x+52 | | 7=-3+3x | | =2x^2+2x-12 | | 4x+10y=1 | | 4x+7+6=-5x-23 | | -(8y+1)-(-7y-6)=1 | | =23x^2-22x | | 7x=84x | | 6(4x-9)=3(8x+5) | | 8+6r-7=7r+3-2r | | 8+6r-7r=7r+3-2r | | =(y-5)(y-3) | | A^3b^2= | | 4c^2+24c+30=0 | | =x^3-27 | | 2x+[3x-2(x-2y)-3x]= | | =15a^2+11a+2 | | 9x+6+4x+x-9= | | -3x-(2-x)=-2(2-3x) | | 13(t-4)+8t=7(3t+5)-8 | | 3(y+5)+5(y-4)+7= | | 15x^2-26x=0 | | 7(x-3)=7-2(3x+1) | | 4(y-5)= | | 9X+7X=81+X | | 3-2(4-x)=5(x+1)+2 | | 4mn-6m+5n-3m+4n-5mn= | | =x^2+19x+2 | | 2(x-3)-(x-2)=2x+3 |